The Relationship between the Myers-Briggs Type Indicator (MBTI) Types and Psychological Well-being among College Students in China - Liying, Wang; Sheibani, Shahnaz (Journal of Ecohumanism, 2024)
Aim: This study explores the relationship between Myers-Briggs Type Indicator (MBTI) personality types and psychological well-being among Chinese college students, examining how cultural factors influence this relationship and identifying key factors impacting students' mental health. Methodology: A systematic literature review was conducted, focusing on peer-reviewed articles from the past decade. Databases such as PubMed, PsycINFO, and Google Scholar were searched using keywords like "MBTI," "psychological well-being," "college students," and "China." Inclusion criteria included studies on MBTI and psychological well-being among Chinese college students. Results: The review found that 64% of extraverted students reported high life satisfaction, compared to 42% of introverted students. Sensing students showed 58% academic satisfaction, while only 45% of intuitive students reported similar satisfaction levels. Thinkers (60%) and feelers (55%) displayed high psychological well-being linked to their respective environments. Judging types reported 70% life satisfaction, whereas only 45% of perceiving types expressed similar satisfaction. These findings underscore the significant impact of MBTI personality types on the psychological well-being of Chinese college students. Conclusion: MBTI types significantly influence psychological well-being among Chinese college students, moderated by cultural, social, and educational factors. Tailored mental health interventions and supportive environments are essential to address the diverse needs of students. Recommendations: Colleges should integrate MBTI-based counseling services, provide flexible learning options, and promote social support networks. These measures will accommodate varying personality types and improve overall student well-being. Implications: Understanding the interplay between MBTI types and psychological well-being within the Chinese cultural context offers valuable insights for educators and mental health professionals. These insights can inform the development of culturally sensitive interventions and support systems, enhancing the mental health and academic success of college students.